The Analysis of Vertical Transaction Behavior and Performance Based on Automobile Brand Trust in Supply Chain - Guanglan Zhou; Yulian Fei; Jun Hu (Discrete Dynamics in Nature and Society)
The nontrust behaviors among the automobile supply chain members lead to a trust crisis situation. Under such circumstances, this paper studies the mutual influences of trust, enterprise behavior, and transaction performance on the independent brand automobile supply chain. The business behavior concept which consists of information sharing, joint action, and specific asset investment is proposed. Then, the paper tests the reliability and validity of the collected data through Structural Equation Modeling (SEM). Through empirical test and analysis on mutual relationship among vertical transaction enterprise behaviors, trust, and transaction performance, the vertical transaction enterprise behaviors can be regulated, so as to improve the efficiency of independent brand automobile supply chain.